2019
DOI: 10.1519/jpt.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Computerized Force Platform Measures of Balance Function in Healthy Older Adults

Abstract: FP measures provided reliable information on balance function in healthy older adults; however, small learning effects were evident, particularly for the SOT. The SEM and MDC95 for the LOS and SOT measures were relatively large for this healthy elderly cohort. A relationship between FP measures, which assess underlying balance mechanisms, and clinical balance and gait measures was not strongly supported in this study. Further research is needed to justify the value of adding FP measures to a test battery for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…The SOT was tested under six sensory conditions: eyes open on a firm surface (SOT1), eyes closed on a firm surface (SOT2), eyes open with sway referenced visual surround (SOT3), eyes open on sway referenced support surface (SOT4), eyes closed on sway referenced support surface (SOT5), eyes open with sway referenced visual surround, and sway referenced support surface (SOT6). The SOT equilibrium score provided a balance score for each condition that reflected the amount of sway in the anterior–posterior direction, where higher scores indicated better balance and less sway [ 35 ]. This score was used in the following analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The SOT was tested under six sensory conditions: eyes open on a firm surface (SOT1), eyes closed on a firm surface (SOT2), eyes open with sway referenced visual surround (SOT3), eyes open on sway referenced support surface (SOT4), eyes closed on sway referenced support surface (SOT5), eyes open with sway referenced visual surround, and sway referenced support surface (SOT6). The SOT equilibrium score provided a balance score for each condition that reflected the amount of sway in the anterior–posterior direction, where higher scores indicated better balance and less sway [ 35 ]. This score was used in the following analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic balance refers to automatic postural responses to center-of-gravity disturbances caused by movement, and a test to track a moving target with COP has been suggested as a dynamic balance test. 32) Harro and Garacia 13) reported similar findings in a sample of 46 healthy community-dwelling older adults with a mean age of 67.67 (5.1) years with no history of falls. The investigators reported that administering the test within a 10-day period for test-retest reliability of limits of stability (LOS) endpoint excursion measurement demonstrated good test-retest reliability (ICC, 0.77; 95% CI, 0.56-0.87), with an SEM of 9.0.…”
Section: Discussionmentioning
confidence: 56%
“…Currently, computerized balance function assessments are increasingly used in the clinical setting in the screening of older adults to assess fall risk and examine balance dysfunction. 13,14) However, they are not standardized within or across settings and lack computerized comprehensive fall risk assessment tools. The Fall Risk Assessment (FRA) system is a new instrument recently developed by Inbody Co., Ltd. (Seoul, Korea) to predict the risk of falls.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while we target at using the VR headset for the saccadic eye movement of neurodegenerative disorders, the device could become an alternative assessment tool in different fields. For example, if the VR headset is combined with a postural assessment device, we could stimulate postural sway with immersive VR environments and achieve a cost-efficient and portable assessment system to measure in a small space, instead of being restricted to dedicated laboratories with non-transportable systems for the balance assessment (47). Future studies integrating the VR device bear potential for assessments of diverse research fields.…”
Section: Potential Of Hmd-vr Technologymentioning
confidence: 99%